Peripheral neuropathy in acrodermatitis chronica atrophicans - a late Borrelia manifestation - Kindstrand, E.; Nilsson, B. Y.; Hovmark, A.; Pirskanen, R.; Asbrink, E. (ACTA NEUROLOGICA SCANDINAVICA, 1997)
Clinical and/or neurophysiological signs of peripheral neuropathy were found in 64% of 63 consecutive untreated patients with the late borrelial manifestation acrodermatitis chronica atrophicans (ACA). The neuropathy frequency was significantly higher in the patients than in 30 age‐ and sex‐matched control persons of whom 27% had neuropathy findings. The most common neuropathy in ACA was a symmetric distal sensory polyneuropathy. In a subgroup of patients with localized or asymmetric neuropathy, the changes were found more often in extremities with than without visible ACA lesions. Neuropathy symptoms, most often pain and/or paresthesia, were present in 64% of the patients, compared to in 13% of the control persons. Thus, both symptoms and signs of neuropathy were significantly more frequent in patients with untreated ACA than in control subjects.